Emosi Tokoh Utama dalam Kumpulan Cerpen Tentang Kita dan Laut Karya Yetti A.K.A (Psikologi Sastra): Emotion Analysis of the Main Characters in the Collection of About Us and the Sea by Yetti A.KA.(Literary Psychology) - Aliffia, Trissanti Nur; Syafroni, Roni Nugraha; Meliasanti, Ferina (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The research has a psychological background that the people experience, namely emotional control. This problem is related to the psychology of the characters in the short About Us and the Sea by Yetti A.KA., especially the emotions that dominate the female characters. Researchers used qualitative descriptive methods referring to literary psychology. Data collection techniques include listening, taking notes and a literature study process. Next, the data is analyzed by collecting, reducing, presenting and drawing conclusions. The results of this research found that from the three short stories analyzed there were 32 character emotional data consisting of 12 basic emotions, 10 emotions related to sensory stimulation, 6 emotions related to self-assessment, and 4 emotions related to other people. There is complete emotional data obtained from the three short stories. The emotions that character often feel are basic emotions with feelings of happiness and sadness dominating.